Karl Polayni, Market Economy and Economic Liberalisation in Nepal - Pandey, Krishna P. (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
This review essay is a short account for Karl Polanyi’s alternative interpretation of the world economic history that largely relies on the comparative analysis of two forms of economic exchanges; non-market and market. The replacement of reciprocity and redistribution produced by the market economy based on the principles of profit making, gain and competition, in which money has a central role, is the key argument that Polanyi brings into consideration. His notion of market economy that is self-regulating by its very nature has been synonymous with the free market practice under economic liberalization policy adopted by the capitalist societies nowadays. Despite his projection of the collapse of the market economy in the future, it is gaining ground along with frequent adjustments, adaptations and compromises with other dynamics of society, which could be considered as a new form of embeddedness. The essay raises few analytical issues embeddedness from Nepal’s exercise of market economy on the backdrop of Polanyi’s notion of self-regulating market. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 11-20